2002
DOI: 10.1039/b206104j
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective epoxidation of olefins catalyzed by Mn (salen)/MCM-41 synthesized with a new anchoring method

Abstract: New immobilization of the chiral Mn(salen) complex through the complexation of managanese by oxygen atoms of the phenoxyl groups grafted on the surface of MCM-41 leads to a markedly higher ee than for the free complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(76 citation statements)
references
References 10 publications
2
73
1
Order By: Relevance
“…It was shown that the Schiff base ligands are able to coordinate many different metals, and to stabilize them in various oxidation states, enabling the use of Schiff base metal complexes for a large variety of useful catalytic transformations such as asymmetric epoxidation [5][6][7][8], asymmetric sulfide oxidation [9,10], cyclopropanation [11], aziridination [12], Knoevenagel condensation [13], and T. Ben Zid Á I. Khedher (&) Á A. Ghorbel Département de Chimie, Faculté des Sciences de Tunis, Laboratoire de Chimie des Matériaux et Catalyse, 1060 Tunis, Tunisie e-mail: ilyeskhadher@yahoo.com selective hydrogenation reactions under homogenous conditions [14,15]. Due to the advantages of heterogeneous catalysis systems, namely easy catalyst/product separation and simple catalyst recycling, the heterogenization of these homogenous chiral catalysts onto several supports has received great attention in recent years [16][17][18][19][20][21][22]. In spite of this, the use of the chiral vanadium salen Schiff base immobilized on inorganic support as asymmetric oxidation catalysts has been rather scarce and has mainly focused on the asymmetric addition of trimethylsilyl cyanide to aldehydes [23].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the Schiff base ligands are able to coordinate many different metals, and to stabilize them in various oxidation states, enabling the use of Schiff base metal complexes for a large variety of useful catalytic transformations such as asymmetric epoxidation [5][6][7][8], asymmetric sulfide oxidation [9,10], cyclopropanation [11], aziridination [12], Knoevenagel condensation [13], and T. Ben Zid Á I. Khedher (&) Á A. Ghorbel Département de Chimie, Faculté des Sciences de Tunis, Laboratoire de Chimie des Matériaux et Catalyse, 1060 Tunis, Tunisie e-mail: ilyeskhadher@yahoo.com selective hydrogenation reactions under homogenous conditions [14,15]. Due to the advantages of heterogeneous catalysis systems, namely easy catalyst/product separation and simple catalyst recycling, the heterogenization of these homogenous chiral catalysts onto several supports has received great attention in recent years [16][17][18][19][20][21][22]. In spite of this, the use of the chiral vanadium salen Schiff base immobilized on inorganic support as asymmetric oxidation catalysts has been rather scarce and has mainly focused on the asymmetric addition of trimethylsilyl cyanide to aldehydes [23].…”
Section: Introductionmentioning
confidence: 99%
“…Li and coworkers have been working in the modification of MCM-41 with organic groups, such as phenoxide and benzenesulfonate (Figure 25), to immobilize Jacobsen's (salen)Mn complex through cation exchange. In a first 5 report, 27 the immobilization with a phenoxide group showed to be positive for the epoxidation of α-methylstyrene with aqueous NaClO, as the enantioselectivity increased from 56% ee in solution to 72% ee with the heterogeneous catalyst, and the placement of the catalytic sites inside the mesopores was 10 demonstrated by the lack of activity of the solid to epoxidize the bulkier 1-phenylcyclohexene.…”
mentioning
confidence: 99%
“…[32] Salen-Mn(III) complexes supported on amorphous silica or MCM-41 catalysts were less effective in the case of styrene, with an ee and epoxide yield of 30% and 70%, respectively. [32] Chiral salen-Mn(III) catalyst when axially immobilised into MCM-41 via either phenoxy [13] or phenylsulphonic group [14] showed higher ee % than the homogeneous counterparts for the epoxidation of a-methylstyrene.…”
Section: Full Papersmentioning
confidence: 97%
“…Subsequent testing of their catalyst in the epoxidation of nonfunctionalised alkenes using NaOCl as oxidant gave a higher ee for certain alkenes than that found under homogeneous conditions. Recently, Li and co-workers [13,14] demonstrated that chiral salen-Mn(III) catalyst when axially immobilised into MCM-41 through complexation of the manganese via the oxygen atoms of the phenoxy groups [13] produced epoxide with 72% ee, whereas the same complex immobilised via a phenylsulphonic group [14] gave a slightly higher ee value for the epoxidation of a-methylstyrene. These phenoxy or phenylsulphonic group-anchored catalysts showed significantly higher % ee than the homogenous analogues (56% ee) for a-methylstyrene epoxidation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation